1996
DOI: 10.1073/pnas.93.16.8584
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations in maturation of secretory proteins and their association with endoplasmic reticulum chaperones in a cell culture model for epithelial ischemia.

Abstract: The effects of ischemia on the maturation of secretory proteins are not well understood. Among several events that occur during ischemia-reperfusion are a rapid and extensive decrease in ATP levels and an alteration of cellular oxidative state. Since the normal folding and assembly of secretory proteins are mediated by endoplasmic reticulum (ER) molecular chaperones, the function of which depends on ATP and maintenance of an appropriate redox environment, ischemia might be expected to perturb folding of secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 47 publications
5
83
0
4
Order By: Relevance
“…ERp72 interacts in itro with denatured proteins in association with molecular chaperones, including PDI, BiP and GRp94 [167,168]. Similar findings have been made in i o for thyroglobulin and another secretory protein, thrombospondin [103,169].…”
Section: Erp72mentioning
confidence: 67%
“…ERp72 interacts in itro with denatured proteins in association with molecular chaperones, including PDI, BiP and GRp94 [167,168]. Similar findings have been made in i o for thyroglobulin and another secretory protein, thrombospondin [103,169].…”
Section: Erp72mentioning
confidence: 67%
“…Previous reports by our and other groups have emphasized a pathogenic role of ER stress in glomerular and tubular epithelial injury. 14,17,20,21 Immunohistochemical analysis in this study showed upregulation of the ER chaperones GRP78 and ORP150 in the glomeruli of rats with antiThy1 nephritis. Furthermore, activation of the PERK pathway, a UPR pathway involved in the downregulation of translation, was also detected in the glomeruli of these rats.…”
Section: Discussionmentioning
confidence: 99%
“…ATP Depletion-Depletion of ATP was achieved rapidly in MDCK cells by using a combination of glycolytic (2-deoxy-D-glucose; Sigma) and oxidative (antimycin A; Sigma) inhibitors, as described previously (15,22,23). In brief, confluent monolayers were washed with PBS three times, then exposed to Dulbecco's PBS containing 1.5 mM CaCl 2 , 2 mM MgCl 2 , 2 mM deoxy-D-glucose, and 10 M antimycin A for various times.…”
Section: Methodsmentioning
confidence: 99%
“…After ATP Depletion, TJ Proteins Fractionate into a Large Macromolecular Complex-The marked insolubility of TJ proteins after ATP depletion suggested that they might associate with other proteins (possibly cytoskeletal), leading us to examine whether large complexes containing TJ proteins could be identified (23,25). When analyzed by rate zonal centrifugation through 5-20% sucrose gradients, after ATP depletion, the amount of detergent (1% Triton X-100, 0.5% deoxycholate, and 0.2% SDS)-extractable ZO-1 as well as ZO-2 present in the high density (fractions 13-17) fractions increased 1.5ϳ2-fold by densitometric analysis (Fig.…”
Section: Atp Depletion Leads To a Reversible Decrease Of Ter In Mdck mentioning
confidence: 99%